THE CULTURE OF 'MAIRIAK' AS A REFERENCE FOR THE LITERARY, CUSTOMARY, AND SOSIAL VALUES OF THE MINANGKABAU PEOPLE IN JORONG BANSA NAGARI KAMANG TANGAH, KAMANG MAGEK DISTRICT, AGAM REGENCY - Istiqlal, Abdul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2024)
The development and advancement of science and technology in the current decade continues to change. One of them is the cultural changes that exist in society. This research tries to examine the culture of “mairiak” as a reference for literary, customary, and social values that exist in the community. The purpose of this research is to search and try to find the cultural value of “Mairiak” which is a reference to literary, customary and social values in the community. The method and type of this research is qualitative research using informants, field presence, and literature study. The informants of this research are people who carry out “mairiak” cultural activities, the author is directly present in the field, and literature studies where the author seeks information in accordance with this research problem in the form of journals, theses, theses, or dissertations and books that have a relationship with this research. In this research, the author limits the problem to the culture of “mairiak” as a reference for literary, customary, and social values. The findings of this research explain the existence of literary, customary, and social values in the community